2018
DOI: 10.1080/19371918.2017.1415180
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Care among Caregivers of Persons Living with HIV/AIDS in Rural Namibia: Correlates and Outcomes

Abstract: This study examined the correlates of burden of caregivers providing care to people living with HIV/AIDS in rural northern Namibia and the consequences of caregivers' burden on their physical health and mental health. A purposive sampling method was used to recruit a total of 97 primary caregivers (N = 97) in rural Namibia. We found that hunger and HIV stigma were both positively associated with caregiver burden. Caregiver burden was positively related to depression and negatively related to quality of life. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 40 publications
2
16
1
1
Order By: Relevance
“…29 Moreover, other studies also stated that perceived stigma had a significant relationship with quality-of-life, where the higher the level of perceived stigma, the lower the quality-of-life for them. 30,31 Caregiver burdens in this study did not have a significant relation with quality-of-life of HIV children. This finding is not in accordance with previous studies, which found a significant relationship between caregiver burden and quality-of-life, where the higher the caregiver burden score, the lower the QoL value of HIV patients.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…29 Moreover, other studies also stated that perceived stigma had a significant relationship with quality-of-life, where the higher the level of perceived stigma, the lower the quality-of-life for them. 30,31 Caregiver burdens in this study did not have a significant relation with quality-of-life of HIV children. This finding is not in accordance with previous studies, which found a significant relationship between caregiver burden and quality-of-life, where the higher the caregiver burden score, the lower the QoL value of HIV patients.…”
Section: Discussionmentioning
confidence: 51%
“…This finding is not in accordance with previous studies, which found a significant relationship between caregiver burden and quality-of-life, where the higher the caregiver burden score, the lower the QoL value of HIV patients. [31][32][33] The difference is possible because the caregiver keeps the health status of children with HIV confidential, 34 which is psychologically very helpful for the caregiver. 7 Their social life also does not experience problems despite many economic problems found in HIV cases.…”
Section: Discussionmentioning
confidence: 99%
“…Mereka harus menyisihkan waktu untuk membantu ODHA beraktivitas sehari-hari, perawatan medis (misal manajemen obat-obatan, mendampingi pasien ke rumah sakit atau puskesmas), dan memberikan dukungan secara emosional dan financial. Menjadi seorang caregiver ODHA membutuhkan penyesuaian lebih lanjut dalam keluarga, pekerjaan dan interaksi sosial (Kalomo & Liao, 2018).…”
Section: Konflik Peranunclassified
“…This literature does link experiences such as symptoms of depression to experiences of interpersonal and domestic violence (Kalomo et al, 2020), depression and HIV-related stigma (Kalomo, 2018), anxiety and HIV (Besthorn et al, 2018), depression among Namibian adolescents experiencing orphanhood (Ruiz-Casares et al, 2009), and general distress among adolescents living with HIV (Gentz et al, 2017, 2018). Critically, this body of literature centers contextual factors in understanding mental health across groups in Namibia by illuminating relationships between HIV and mental health (Gentz et al, 2017, 2018), experiences like gender-based violence (Kalomo et al, 2020), and caregiver involvement in health care (Kalomo & Liao, 2018). Absent and outside of the scope of these valuable studies, however, is attention to explanatory models of mental illness within Namibian cultural groups.…”
Section: Mental Illness and Psychological Services In Namibiamentioning
confidence: 99%
“…Family values and beliefs are also viewed as crucial aspects in informing what an individual may believe about treatment (Bartholomew, 2018). Further, related empirical efforts in Namibia have incorporated family members and caregivers (e.g., Kalomo & Liao, 2018) and others have drawn attention to close familial relationships among the Aawambo (e.g., Brown, 2011). Taken together with family roles in mental illness and treatment seeking (Bartholomew, 2018; Bartholomew & Gentz, 2019) and similar efforts in health research (Kalomo & Liao, 2018), inclusion of family members in these cases will help further illuminate the experience of omunanamwengu .…”
Section: Current Studymentioning
confidence: 99%